MAKNA SIMBOLIK TURUN BONIAH SEBAGAI KEARIFAN LOKAL MASYARAKAT DESA PULAU INGU KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Mardiatul Aulia; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Turun boniah is carried out before planting rice in the rice fields. One interesting aspect of the tradition is to go down turun boniah in Pulau Ingu village, Benai Subdistrict, apart from the fact that the tradition is still preserved and used as local wisdom by the local village community, as well as the implementation process. Seedling descent process consists of two stages, consisting of the preparation stage, and the implementation phase. Every step down there is a symbol that can be interpreted one by one. The purpose of this study was to find out the meaning of symbolic situations, products of social interaction and interpretation of tradition turun boniah  as local wisdom of the people of Pulau Ingu village, Benai District, Kuantan Singingi Regency. The method used in this study is qualitative with a symbolic interaction approach. The informants in this study were 7 people, consisting of traditional / community leaders 2 people, 2 people perpetrators and 3 people in general. Data collection techniques used were observation, interviews, and documentation. The results of the study showed that the meaning of the symbolic situation in the religious community in Ingu Island consisted of physical objects and social objects. The physical object in the boniah descent on the island of Ingu is, among others, water concoctions and tools that use the turun boniah  drop. The social object in the turun boniah  descends is the prayer and spell down . The meaning of the product social interaction, including the overall downward meaning of different perspectives from each informant. The figure is interpreted by the perpetrators as a tradition that must be preserved. The procession of turun boniah  is interpreted by traditional leaders as culture, customs that must continue to live, obedience to ancestors. The procession of turun boniah  is interpreted by the people of Pulau Ingu to have a different view on the meaning of the turun boniah . The meaning of the turun boniah  interpretation in Pulau Ingu Village includes open actions and closed actions. Closed action is related to motivation and feeling. Outdoor action actors turun boniah  include compact attitude and togetherness, as well as facial expressions of joy and happiness visible actors as well as expressions of emotional closeness between actors.